Visual spectral sensitivity of algae octopus, Abdopus aculeatus (d'Orbigny, 1834) and the effect of lure color on the capture process and performance of a simple handline Into-into used in Sibunag, Guimaras, Philippines - Fernandez, Jumari C (Miagao, Iloilo University of the Philippines Visayas, 2021)
Octopus fishing is one of the major fishing activities that generate income for fishers of algae octopus Abdopus aculeatus in barangay Sabang, Guimaras. A white-colored lure of simples octopus handline "Into-into" was traditionally used by local fishers who never tried using another ncolor. Five different lure colors (red, blue, white, green, and brown) and three sizes (small, medium, large) were evaluated in the study. The stages of the catch process when using the Into-into were evaluated through interviews, direct observation, and recorded videos using a digital single-lens reflex (DSLR) camera. The effect of different colors and sizes of the lure was determined by evaluating the number and sizes of octopus catch. The capture process involves four steps: attraction, attachment, escapement, and capture. With the traditional white-colored lure 10% are usually attracted, 3% escape, and 7% are captured. Lure color has a significant effect (ANOVA, p,.001) on the number of octopus catch, and green (LSD post-hoc method, p,0.01) and blue (LSD post-hoc method, p,0.05) colored lures are more effective in capturing octopus than the traditional white-colored lure, which in turn is more effective than the two other colors of the lure tested, red and brown. Therefore, either green or blue colored lures may be used by the local fishers since there is no significant difference betwen these colors (LSD post hoc method, p.0.05). On (ANOVA, p.0.05). In terms of the effect on the sizes of catch, both the color and size of the lures in a simple octopus handline have no significant effect (ANOVA, p.0.05). The attraction with green and blue colored lure seems to match with the maximum absorption of A. aculeatus retina and in most octopus species.
Thesis (M.S. Fisheries-Fisheries Biology) -- Miagao, Iloilo : University of the Philippines Visayas, March 2021.
Keywords: Absorption spectra; Simple Octopus handline "Into-into".